Fatigue-induced alterations of the patellar tendon in elite sprint track cyclists - Klich, S.; Michalik, K.; Rajca, J.; Ficek, K.; Fernández-de-las-Peñas, C.; Kawczynski, A.; Madeleine, P. (International Journal of Sports Medicine, 2023)
This study aims to investigate morphological and mechanical properties and echogenicity of the patellar tendon (PT) after acute fatigue-induced alterations in sprint track cyclists. Fourteen elite track cyclists participated in this study. The exercise protocol consisted of three maximal start accelerations (over a distance of 62.5 m), one maximal start acceleration (at both 125 m and 250 m), and sprints from the standing start. Immediately after testing all measurements, PT stiffness and thickness were set at 5-10-15-20 mm distal from the apex of the patella and 5-10 mm proximal to the tibial tuberosity. CSA was set at proximal, middle, and distal, while echogenicity was at proximal and distal points. The results showed significant increases in PT stiffness at all reference points after start acceleration (p<0.001). PT thickness showed similar results for stiffness, except for location placed at TT-5 (p<0.001). CSA increased significantly in proximal, middle, and distal regions (p<0.001), while echogenicity of the tendon increased in proximal and distal regions (p<0.001) after start acceleration. Regional-dependent alterations of PT thickness and stiffness may be related to anatomical and physiological mechanisms due to acute isometric contraction in the initial phase of standing start. Tendon echogenicity might be also useful in monitoring tendon mechanical properties and defining acute fatigue-induced changes.